PENGARUH HIKAYAT PERANG SABIL TERHADAP SEMANGAT PERJUANGAN RAKYAT ACEH DALAM PERANG ACEH MELAWAN BELANDA (1873-1903) - sri wahyuni, sri wahyuni; Anis, Madhan (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Kependidikan, 2022)
This study aims to examine the background of the emergence of the sabil war saga and examine the influence of the sabil war saga on the spirit of the Acehnese people's struggle in the Aceh war against the Dutch (1873-1903). The method used is the historical method, so the steps used in this study include heuristics, source criticism, interpretation, and historiography. Based on the results of the study, it was concluded that in Aceh's war against the Dutch, it gave birth to its own mentality for the people of Aceh, there was resistance to maintain the dignity of the state while at the same time upholding the religion of Islam. The background of the emergence of the sabil war saga was during the Aceh war against the Netherlands. In the face of a prolonged war the sabil war saga became a kind of belief that became a source of strength, enthusiasm, and courage against the presence of the Dutch. Sabil war is jihad fisabilillah against all forms of colonialism that interfere with the religion of Islam and its homeland. The great influence of the sabil war saga has succeeded in igniting the spirit of jihad fisabilillah and is considered a very dangerous subversive work. The law of stable war is fardhu ain, which is obligatory on all believers, men and women, young and old, including children. Keyword: saga, sabil war, spirit of struggle, the people of Aceh.